Efektifitas Kebijakan OJK Terkait Buyback Saham Terhadap Perubahan IHSG Di Masa Pandemi Covid-19 - Septiana Septiana (AGHNIYA : Jurnal Ekonomi Islam, 2020)
The covid-19 pandemic affected of Indonesia Composite Index (IHSG) decline, to minimize the impact of covid-19 the financial services authority (OJK) made a shares buyback policy. Share buyback is repurchase of stock by an issuer that issues share on astock exchange with the aim of reduce outstanding shares to be able to reduce a significant share price decline. This working paper will focus on the effectiveness of financial services authority policies related to share buyback on changes of composite index during the covid-19 pandemic, using qualitative research methods and analiytical descriptive. Indonesia Composite Index (IHSG) has decreased greatly since early thisyears until March, but now it’s slightly better despite the changes less significant but can suppress further decline in stock price.